Pondok Persulukan Ma’arif Muslimin: Saksi Bisu Penyebaran Ajaran Tarekat Naqsabandiyah di Kota Padangsidimpuan - Sida Wati Rambe; Yusra Dewi Siregar; Anang Anas Azhar (Warisan: Journal of History and Cultural Heritage, 2021)
This article discusses the history and development of the Persulukan Ma'arif Muslimin in the city of Padangsidimpuan. The long history of the arrival of the Naqsabandiyah teachings in the southern Tapanuli region was manifested in the form of religious activities at Pondok Persulukan. This research uses qualitative research methods with two approaches; historical and social approaches. In this research, the writer wants to examine how this Persulukan Pondok is one of the places for spreading the teachings of the Naqsyabandiyah Order in the city of Padangsidimpuan. Apart from that, the writer also wants to see what developments have been since the presence of Pondok Persulukan Ma'arif Muslimin. Pondok Persulukan Ma'arif Muslimin was founded in 1970 by Sheikh Imom Daulay. The Pondok Persulukan has experienced ups and downs in its journey. At the beginning of its establishment, Pondok Persulukan also had an educational institution (pondok pesantren), but due to several reasons, the boarding school was no longer operational. During its development, Pondok Persulukan changed its name to the Ma'arif Muslimin Padangsidimpuan Social Welfare Institution. Until now, Pondok Persulukan is still used by the local community as a place to study religious sciences, especially for those who are elderly.